Investment Feasibility and Strategic Development Scenarios of Yogyakarta-Bawen Toll Road - Danubroto, Radyo Wijoyo; Malkhamah, Siti; Amrozi, Muhammad Rizka Fahmi (Universitas Negeri Yogyakarta, 2024)
This study examines the feasibility of the investment in the Yogyakarta-Bawen toll road project by analyzing traffic conditions, expenditure costs, toll revenues, and investment value. Simulation using PTV Visum shows a significant increase in the volume-to-capacity ratio (VCR) on the national road sections around the toll road until 2061. The modeling result also indicates that the operation of the toll road reduces traffic loads on several surrounding national road sections with a decrease in VCR. The analysis results reveal a negative net present value (NPV) amounting to -Rp.506,560,648,100, and an internal rate of return (IRR) of 11.49% is under the discount rate (12.03%). In the tariff adjustment scenario, the project shows an IRR of 12.48% with an NPV of Rp 575,501 million, and the payback period (PBP) is achieved after 16 years. In the concession adjustment scenario, the IRR is 12.12% with an NPV of Rp 123,461 million, and the PBP is achieved after 17 years. Meanwhile, the tariff and concession adjustment scenario show an IRR of 12.48% with an NPV of Rp 652,033 million, and the PBP is achieved after 16 years. Based on the investment feasibility evaluation, the recommended best strategy is tariff adjustment. This strategy allows for an optimal increase in toll revenue and investment returns. It is expected that the Yogyakarta-Bawen toll road project can achieve better investment feasibility and provide long-term benefits to investors, road users, and the overall community.